Oral Interaction Through Task Based Learning - Rangel, Jeiny Silva (Revista Perspectivas Educativas, 2015)
The document aims to explore oral interaction by designing curricular units founded on task-based learning. It was carried out in a public school with sixth graders between the ages of 11 to 14 years old in Barrancabermeja Colombia. This paper analyzes the behavior of students to perform oral activities and the importance of designing authentic material in English for public teachers. The data gathering revealed that these curricular units moved the teacher-student interaction to studentstudent interaction; the students’ oral interactions contributed to know their weaknesses in the structure of the language and they began to take different roles in their English learning.